Factors Determining Foreign Direct Investment In DKI Jakarta Indonesia - Agus Tri Basuki; Syahdatunisia Fidela Rahman (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to analyze the factors that influence foreign investment in DKI Jakarta, Indonesia. In this study using the Vector Error Correction Model approach. The data used in this research is time series data for the period 1980-2021 originating from the Indonesian Central Bureau of Statistics, the Investment Coordinating Board, and the World Development Indicators (WDI). The estimation results show that in the short term the GRDP and inflation variables have a positive and significant effect on foreign investment, while the exchange rate and labor variables have no effect on foreign investment. In the long run the GRDP variables and inflation variables have a positive and significant effect on foreign investment, the exchange rate variable has a negative and significant effect on foreign investment, and the number of workers has no effect on foreign investment. The regional government together with the Indonesian central bank are expected to be able to maintain economic stability through inflation targets and a conducive exchange rate of the rupiah against foreign currencies, so as to encourage FDI that is pro-employment.